Dual antiplatelet therapy of clopidogrel plus aspirin versus aspirin monotherapy in patients with Coronary Artery Disease (CAD): a systematic review and meta-analysis - Haidar Ali Hamzah; Theodorus (Journal of Indonesia Vascular Access, 2022)
Background: Aspirin is the most commonly used for treatment in patients with coronary artery disease (CAD). However, there are many evidences from several trials suggested that dual antiplatelet therapy (DAPT) might exhibit a better outcome and more effective than aspirin monotherapy. Thus, we aimed to assess the effect of DAPT versus aspirin monotherapy in patients with CAD. Methods: Electronic databases were performed in PubMed, EMBASE, and Cohrane from Januari 2005 until March 2021. We searched for randomized control trials comparing DAPT versus aspirin monotherapy in patients with CAD. Pooled effects estimates were reported as an odds ratio (OR) with 95% confidence intervals (CI) and calculated using random effects model. RevMan 5.4 software was used for data analysis. Results: Five randomized control trials with a total of 8,203 participants met the inclusion critera. DAPT was found to have an association in reducing the risk of major adverse cardiovascular events (OR 0.72; 95% CI 0.57-0.90; p = 0.003; I2 = 17%) and death events (OR 0.62; 95% CI 0.49-0.79; p < 0.0001; I2 = 0%)  compared with aspirin monotherapy. Yet, there were no significant difference in myocardial infarction events (OR 0.78; 95% CI 0.57-1.07; p = 0.13; I2 = 28%) and bleeding events (OR 1.65; 95% CI 0.97-2.81; p = 0.06; I2 = 0%) between two groups. Conclusions: DAPT treatment has a significant effect in reducing the risk of major cardiovascular and death events without a significant effect in myocardial infarction and bleeding events compared with aspirin monotherapy.